Grain yield and leaf gas exchange in upland NERICA rice under repeated cycles of water deficit at reproductive growth stage - Suleiman, S.O.; Habila, D.G.; Fofana, M.; Abolanle, B.M.; Olatunbosun, A.N. (Elsevier, 2022)
New Rice for Africa (NERICA) was reported to have higher exudation and transpiration rates, above ground dry matter at heading than Japanese cultivars. Information on the expression of their gas exchange attributes and water balance under repeated cycles of water deficit at reproductive stage is unknown. This investigation tested the hypothesis that variation in leaf gas exchange and energy attributes of NERICA rice under repeated cycles of water deficit at reproductive stage would affect their performance under field conditions. Repeated cycles of water regimes (irrigation and water deficit) at reproductive stage were imposed on eight NERICA rice (NERICA 1–8) and checks (CG14, WAB56–104 and IR64). Water regimes were assigned to main plots and rice cultivars to sub-plots using randomised complete block design with three replicates. Drought-tolerant NERICA 4 and 7 had significantly higher relative water content, stomatal conductance, leaf photosynthetic rates with the least canopy temperature than others. A converse pattern was observed in the drought-susceptible IR 64. Grain yield of NERICA 4 and 7 was significantly higher than that of IR 64. These results suggested that improved water and energy status observed in NERICA 4 and 7 could have been responsible for its better performance than IR 64.